2012
DOI: 10.1002/mnfr.201100689
|View full text |Cite
|
Sign up to set email alerts
|

The Glu298Asp single nucleotide polymorphism in the endothelial nitric oxide synthase gene differentially affects the vascular response to acute consumption of fruit and vegetable puree based drinks

Abstract: Scope: Diets low in fruits and vegetables (FV) are responsible for 2.7 million deaths from cardiovascular diseases (CVD) and certain cancers annually. Many FV and their juices contain flavonoids, some of which increase endothelial nitric oxide synthase (eNOS) activity. A single nucleotide polymorphism in the eNOS gene, where thymine (T) replaces guanine (G) at position 894 predicting substitution of glutamate for aspartate at codon 298 (Glu298Asp), has been associated with increased CVD risk due to effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 79 publications
2
10
0
Order By: Relevance
“…It is therefore possible that, similar to the findings of George et al [32], NZBC anthocyanins influence vascular responses differently based upon genotype. George et al [32] observed that vasodilation in the forearm following acute consumption of a high flavonoid fruit and vegetable puree drink was different for expressions of the eNOS gene Glu298Asp, whereby there was higher endothelium-dependent vasodilation in response to acetylcholine 180 min after intake in GG individuals compared to GT. Therefore, different expressions of this gene may explain the variation in responses in the present study.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is therefore possible that, similar to the findings of George et al [32], NZBC anthocyanins influence vascular responses differently based upon genotype. George et al [32] observed that vasodilation in the forearm following acute consumption of a high flavonoid fruit and vegetable puree drink was different for expressions of the eNOS gene Glu298Asp, whereby there was higher endothelium-dependent vasodilation in response to acetylcholine 180 min after intake in GG individuals compared to GT. Therefore, different expressions of this gene may explain the variation in responses in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, different expressions of this gene may explain the variation in responses in the present study. What is more, George et al [32] measured vasodilation by laser Doppler imaging with iontophoresis on the forearm, therefore measurements made in a peripheral vessel are not representative of generalised endothelial function. Lastly, George et al [32] measured acute responses and it is unknown if repeated supplementation over 7-days, as in the present study, would modulate these responses and is, therefore worth future study.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps similar to what George et al (14) previously demonstrated, there is a differential response to the MC concentrate that is potentially based on genotype. They showed that acute consumption of a flavonoid-rich drink resulted in a considerable increase in dilation of the microcirculation in the forearm in response to acetylcholine after 180 min in GG individuals alone.…”
Section: Discussionsupporting
confidence: 52%
“…Epidemiologic studies have suggested that polyphenol-rich foods can exert positive cardiovascular health benefits (4-6) on blood pressure (BP) (7), insulin resistance (8), cholesterol concentrations (9), and platelet activity (10), which are thought to be attributable to the high phytochemical content in fruits and vegetables (11). Several studies have investigated these cardiovascular health benefits of polyphenolic-rich foods; for example, George et al (12)(13)(14) examined the acute and chronic effects of a fruit and vegetable puree-based drink on vascular function and other CVD risk factors and showed that endotheliumdependent vasodilation was greatest at 3 h after consumption. In addition, Dohadwala et al (15) demonstrated improvements in arterial stiffness and brachial artery flow-mediated dilation at 4 h after cranberry juice consumption.…”
Section: Introductionmentioning
confidence: 99%
“…TMAO also downregulates the expression of anti‐inflammatory cytokine IL‐10, which can protect endothelium cells from damage from increased inflammation and oxidative stress (). In addition, TMAO significantly aggravates the responses of oxidative stress, leading to generation of reactive oxygen species (ROS) and reduction of nitric oxide (NO), which exerts negative effects in maintaining the normal vascular function (). Furthermore, TMAO damages the self‐repairing capacity of injured endothelial cells ().…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%